O uso de plantas medicinais em um território quilombola do município de Mostardas - Rio Grande do Sul. - Vanini, Marisa (2010)
The use of medicinal plants is attached to civilization since the beginning and is part of the culture of a people. The objective of this study is to know what the quilombola community believes about health care related to medicinal plants and understand, from the dialogue in common, the practice of desirable health-related medicinal plants. It is a qualitative study where data were gathered in the quilombola community Teixeiras, in Mostardas, Rio Grande do Sul state. Twenty-two people were questioned with semi-structured interviews and seven people were questioned in a focus group, between July 2008 and June 2009. The criteria used for subject selection were: belonging to the quilombola community, use any medicinal plant, to be more than 18 years old, agree to participate in the study and agree to sign an informed consent. By Gadamer s hermeneutics referential emerged some recording units for subsequent data analysis presenting the quilombola community Teixeiras and their ancestors , medicinal plants, preparation methods and the quilombola official and non official system health care and the medicinal plants in the vision of the quilombolas. Community Teixeiras, beyond the official health system with the Family Health Strategy (FHS), has peculiar ways of care, such as the use of medicinal plants. The questioned subjects want a rapprochement between the knowledge about the use of medicinal plants and the care provided by professionals in the official health system. Knowledge of empirical practices of the people allows understand their culture and the use of natural resources, contributing to the promotion of folk medicine, and generate information about the health of the local community and its own form of care.